Impact of socio-demographic risk factors for prediabetes in two different ethnic backgrounds in Skopje - Penshovska Nikolova, Vera (SHMSHM / AAMD, 2019)
Introduction and Objectives: To establish the possible persistence of the association between certain socio-demographic risk factors and the occurrence of prediabetes in two different ethnic backgrounds in Skopje, Macedonia. Prediabetes is the precursor stage before diabetes mellitus in which not all of the symptoms required to diagnose diabetes are present, but blood sugar is abnormally high. This stage is often referred to as the "grey area".(1) It is not a disease; the American Diabetes Association says,(2) "Prediabetes should not be viewed as a clinical entity in its own right but rather as an increased risk for diabetes and cardiovascular disease (CVD). Prediabetes is associated with obesity (especially abdominal or visceral obesity), dyslipidemia with high triglycerides and/or low HDL cholesterol, and hypertension."(2) It is thus a metabolic diathesis or syndrome, and it usually involves no symptoms and only high blood sugar as the sole sign. Impaired fasting blood sugar and impaired glucose tolerance are two forms of prediabetes that are similar in clinical definition (glucose levels too high for their context) but are physiologically distinct.(3) Insulin resistance, the insulin resistance syndrome (metabolic syndrome or syndrome X), and prediabetes are closely related to one another and have overlapping aspects. Prediabetes develops when the body becomes insulin resistant or unable to use insulin.(5) Some risk factors for diabetes are family history of diabetes, cardiovascular disease, increased triglyceride levels, low levels of HDL (good cholesterol), obesity, elevated blood pressure,(6) elevated fasting plasma glucose,(6,7) women who have had gestational diabetes, had high birth weight babies (greater than 9 lbs.), and/or have polycystic ovarian syndrome (PCOS).(8) These are associated with insulin resistance and are risk factors for the development of type 2 diabetes mellitus. Those in this stratum (IGT or IFG) are at increased risk of cardiovascular disease. Of the two, impaired glucose tolerance better predicts cardiovascular disease and mortality. (9;10;11) In a way, prediabetes is a misnomer since it is an early stage of diabetes. It now is known that the health complications associated with type 2 diabetes often occur before the medical diagnosis of diabetes is made.(12) Materials and Methods: This 17-months retrospective case-control study included patients who performed OGTT (Oral Glucose Tolerance Test) for the diagnosis of diabetes in two polyclinics over a period of 8 and a half months: In the period from 10 06 2018 until 10 02 2019 in the Polyclinic Jane Sandanski Health Home Skopje and in the period from 10 09 2017 to 09 06 2018 in the Polyclinic Bitpazar Health Home Skopje. Patients in both polyclinics were divided into two groups: patients with positive OGTT (study group) and patients with negative OGTT (control group). The socio-demographic factors we analyzed were: gender, nationality, age, BMI, family history of diabetes and smoking status. Results: In the Bitpazar polyclinic out of a total of 54 patients with a derived OGTT with a positive OGTT or impaired glucose tolerance were 37 patients (68.51%) and with a negative OGTT 17 (31.48%) patients
Keywords: oral glucose tolerance test; risk factors; minor